The differences of kinematic parameters high jump between male and female finalists World Championship Daegu, 2011 - Ratko Pavlovic (Turkish Journal of Kinesiology, 2017)
Kinematic parameters often crucially influence the performance in athletic disciplines. This is especially evident for top athletes who have almost identical morphological, motor and functional parameters. The differences that affect the sporting result are generally attributed to a better performance technique that is often the consequence of the different values of the individual's kinematic parameters. This study analyzes the differences between the defined kinematic parameters in the discipline high jump. The sample included 6 men and women athletes who competed in the finals of the World Championships (Daegu, 2011) and a total of 11 kinematic parameters were selected. The results were obtained by applying the T-test module for small independent samples, confirming the differences between men and women's finalists in Daegu, 2011. Statistically significant differences were recorded only in four (4) out of eleven (11) kinematic parameters (36%). Significant differences were recorded in the following parameters where the motor abilities (speed and explosive power) were manifested: maximum body center height (T=6.870; p<0.05), maximum horizontal velocity of the body center (T=3.134; p<0.05), the horizontal velocity of the center of gravity of the body (T=3.087; p<0.05) and the vertical velocity of the center of gravity of the body (T= 15.844; p<0.05).